Un grillo en Times Square - Selden, George, 1929-1989.; Williams, Garth (New York : Farrar, Straus & Giroux, 1992)
The adventures of a country cricket who unintentionally arrives in New York and is befriended by Tucker Mouse and Harry Cat.
Keywords: Crickets -- Fiction; Mice -- Fiction; Cats -- Fiction; Grillos -- Novela juvenil; Ratones -- Novela juvenil; Gatos -- Novela juvenil